2021
DOI: 10.1038/s41598-021-95624-0
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic investigation of the effect of graphene oxide on mechanical properties of cell and actin cytoskeleton networks: experimental and theoretical approaches

Abstract: Biomechanical and morphological analysis of the cells is a novel approach for monitoring the environmental features, drugs, and toxic compounds’ effects on cells. Graphene oxide (GO) has a broad range of medical applications such as tissue engineering and drug delivery. However, the effects of GO nanosheets on biological systems have not been completely understood. In this study, we focused on the biophysical characteristics of cells and their changes resulting from the effect of GO nanosheets. The biophysical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…Changes in the microenvironment have also been also shown to affect the actin cytoskeleton. Recent studies have suggested that exposure to nanomaterials, in particular carbon-based nanomaterials (i.e., single-wall carbon nanotubes (SWCNT), graphene oxide, and graphene), can modulate actin polymerization [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the microenvironment have also been also shown to affect the actin cytoskeleton. Recent studies have suggested that exposure to nanomaterials, in particular carbon-based nanomaterials (i.e., single-wall carbon nanotubes (SWCNT), graphene oxide, and graphene), can modulate actin polymerization [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a molecular dynamics (MD) simulation has shown that actin monomers adhere to graphene via weak interactions, including van der Waal forces, electrostatic interactions, and hydrogen bonding [ 34 ]. These interactions are not strong enough to dissociate two actin monomers compared to graphene oxide (GO) and reduced graphene oxide (rGO) [ 16 , 17 ], of which functional groups on graphene oxide can form hydrogen bonds with oxygen-containing residues in actin [ 34 ], thereby inducing actin disassembly [ 16 , 17 ]. While the effects of graphene on the actin cytoskeleton have been reported at the cellular level, how graphene modulates actin filament assembly is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, traditional twodimensional cell culture approaches are still being used as a route for the risk assessment of nanomaterials and chemical agents [16][17][18][19]. While 2D cell culture platforms will remain an attractive research strategy to investigate basic cellular behaviors [20,21], these simple two dimensional in vitro cell-based assays are not suited to address more complex biological questions where cellular responses, cell-to-cell, and cell-to-matrix interactions are governed by the tissue-specific architecture [17,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This aspect is particularly important by nanomaterial-biology interactions where the uptake, transport, and distribution can be directly linked to the shape, composition, and size of the tissue structure [25]. Hence, the requirement for high-throughput and cost-effective preclinical cell-based assays for assessing the risk of nanoparticles and nanodrug screening studies needs to also involve functional 3D-tissue structures [1,2,21] that can bridge the gap between in vivo and in vitro models [6,26]. Here, three-dimensional spheroid models that are generated either by using commercial microplates, microfluidics systems [4] are ideally suited to address nanomaterial-biology interactions that require adequate cell-to-cell interactions and appropriate cell signaling events [3,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation